Antibacterial Activity of Crude Ethanolic Leaves Extract of Artocarpus heterophyllus Lam. Cultivated in Toba Region against Staphylococcus aureus - Ayu Sibagariang; Muhammad Andre Reynaldi; Rony Sitohang (International Journal of Health Engineering and Technology, 2023)
Jackfruit leaves (Artocarpus heterophyllus Lam.) was tested for its antibacterial activity against a human pathogenic bacterium, Staphylococcus aureus in vitro. Jackfruit leaves were collected from a forest region in the Toba Regency, North Sumatra and air-dried for five days. The dried leaves were crushed into powder to obtain simplicia and macerated using EtOH. The crude extracts were concentrated in vacuo using a rotary-evaporator and diluted into various concentrations (25, 50, 75, 100%) for antibacterial assay. The results showed that the antibacterial activity of extracts followed a concentration-dependent manner with the highest inhibition as expressed in the diameter of inhibitor zone reached 19 mm. The MIC50 value generated from a linear regression analysis between diameter of inhibition zone and concentration was determined at 10% of extract to display its effective concentration. The findings may be further investigated through phytochemical analysis and the selection of different organic solvents to maximize the bioactivity of jackfruit from this region.